2021
DOI: 10.20527/jss.v4i6.4610
|View full text |Cite
|
Sign up to set email alerts
|

Pendapatan Masyarakat Desa Mandiangin Barat Dari Hasil Hutan Bukan Kayu (Hhbk) Di KHDTK Universitas Lambung Mangkurat

Abstract: Forest is a unity of ecosystems on a wide expanse of land containing biological natural resources. Non-timber forest products called HHBK are products sourced from forests other than wood in the form of vegetable objects such as rattan, nipah, sago, bamboo, sap-sap, grains, leaves, medicines and others as well as animals such as wildlife and parts of the wildlife (horns, skins, etc.). Special Purpose Forest Area (KHDTK) is a forest area intended for research and development, education and training, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was reported that in Gempolan Village, Karanganyar Regency, NWFPs from community forest contributed 40.5% to the revenue of community [2]. A similar situation occurred in Mandiangin Barat Village, Banjar Regency where NWFPs contributed 42.94% of the community income [3]. The income generated from NWFPs in Halaban Village, Lima Puluh Kota Regency surpasses that of the previous location [4].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…It was reported that in Gempolan Village, Karanganyar Regency, NWFPs from community forest contributed 40.5% to the revenue of community [2]. A similar situation occurred in Mandiangin Barat Village, Banjar Regency where NWFPs contributed 42.94% of the community income [3]. The income generated from NWFPs in Halaban Village, Lima Puluh Kota Regency surpasses that of the previous location [4].…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, each variable was tested by using the t-test to determine its significance level. The regression equation model was used to determine the effect of the independent variables on the dependent variable (3).…”
Section: Methodsmentioning
confidence: 99%